Optimal disability assistance when fraud and stigma matter - Laurence Jacquet (Queen's University, Department of Economics, 2006)
I study the optimal redistributive structure when individuals with distinct productivities also differ in disutility of work due to either disability or distaste for work. Taxpayers have resentment against inactive benefit recipients because some of them are not actually disabled but lazy. Therefore disabled people who take up transfers are stigmatized. Their stigma disutility increases with the number of non-disabled recipients. Tagging transfers according to disability characteristics decreases stigma. However, tagging is costly and imperfect. In this context, I show how the level of the per capita cost of monitoring relative to labour earnings of low-wage workers determines the optimality of tagging. Under mild conditions, despite their stigma disutility, inactive and disabled people get a strictly lower consumption than low-wage workers. The results are valid under a utilitarian criterion and a criterion which does not compensate for distaste for work.
Keywords: H21; H53; I3; 330; Tagging; Disability benefit; Fraud; Stigma